Powering the green economy : the feed-in tariff handbook - Mendonca, Miguel; Jacobs, David; Sovacool, Benjamin K. ([S.l.] : Routledge, 2009)
Effective policy is vital for creating greener economies, new jobs and industries, for securing energy supplies and for protecting the climate and environment. As renewable energy is fundamental to achieving all of these objectives, it too needs the best possible policy to drive it. Feed-in tariffs have proven to deliver the fastest, most cost-effective and inclusive deployment, by allowing anyone to sell renewable energy into the grid and get a long term, guaranteed return for it. This book, from authors who have spent years working on feed-in tariff design and advocacy, provides a broad and detailed resource on feed-in tariffs and other renewable energy support schemes. It shares many lessons on good and bad design and implementation, as well as discussing the challenges faced by policy, and renewable energy in general. Powering the Green Economy: - Situates renewable energy and feed-in tariffs within the context of the global moves towards a green economy - Provides an introduction to feed-in tariffs and brings developments in key countries around the world up to date - Investigates effective design for developed and emerging economies - Explores technical, social and political issues - Analyses other support schemes - Describes the barriers to renewable energy - Presents a blueprint for campaigning successfully for feed-in tariffs Written in a clear, practical style, this is a must-read for policymakers, businesses, investors, campaigners, academics, community groups and anyone concerned with creating successful and sustainable energy policy.
Keywords: Energy development--Environmental aspects; Energy development--Environmental aspects; Energy development--Environmental aspects--Government policy; Energy development--Environmental aspects--Government policy; Energy development--Government policy; Energy development--Government policy; Energy industries--Prices; Energy industries--Prices; Energy policy--Environmental aspects; Energy policy--Environmental aspects; Renewable energy sources--Government policy; Renewable energy sources--Government policy